2014
DOI: 10.1111/his.12333
|View full text |Cite
|
Sign up to set email alerts
|

Do columnar cell lesions exist in the male breast?

Abstract: We found no lesions with convincing CCL morphology at the periphery of invasive male breast cancers, in gynaecomastia or in normal male breast specimens. Although we cannot completely exclude the existence of CCLs in the male breast, these lesions seem to be very uncommon and are therefore unlikely to play a major role in male breast carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…This paralleled the observation in female breast, wherein the CCLs were also negative for CK5/6 3 5. Recently, three cases of single ducts with monotonous columnar-like cells with hyperplastic features in male breast that were clonally negative for CK5/6 and CK14 were reported 14. These three cases were morphologically similar to the case with focal hyperplasia with atypia in the current series, which was also negative for CK5/6.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This paralleled the observation in female breast, wherein the CCLs were also negative for CK5/6 3 5. Recently, three cases of single ducts with monotonous columnar-like cells with hyperplastic features in male breast that were clonally negative for CK5/6 and CK14 were reported 14. These three cases were morphologically similar to the case with focal hyperplasia with atypia in the current series, which was also negative for CK5/6.…”
Section: Discussionsupporting
confidence: 88%
“…CCLs in the female breast tend to show intraluminal calcifications or secretions,2 but these features have not been identified in the lesional foci, an observation echoed by another study 14. Calcification in CCLs is related to secretion accumulation,17 and osteopontin produced by histiocytes is a crucial mediator 18.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of CCL was similar in malignant and benign lesions [11]. Another recent study found no CCL around invasive cancer, gynaecomastia and normal breast tissue [12]. …”
Section: Discussionmentioning
confidence: 87%
“…Of interest as a potential interpretative pitfall, in some cases we found the presence of columnar cell‐like changes, as described by Ni et al ., to also be CK5/6‐negative and diffusely ER‐positive. Although the debate as to whether columnar cell lesions truly exist in the male breast is ongoing, our experience shows that there are ductal changes that occur in the male breast that at least mimic the cytological and immunohistochemical features of columnar cell lesions in females . Their mention here is to indicate the possibility of misinterpreting them as ADH or DCIS by placing too much emphasis on the immunohistochemical staining pattern.…”
Section: Discussionmentioning
confidence: 93%